Luteinizing Hormone Suppression by Progestin-Primed Ovarian Stimulation Is Associated With Higher Implantation Rate for Patients With Polycystic Ovary Syndrome Who Underwent in vitro Fertilization/Intracytoplasmic Sperm Injection Cycles: Comparing With Short Protocol - Chen, Chen; Yu, Sha; Yu, Weina; Yan, Zhiguang; Jin, Wei; Si, Jiqiang; Li, Menghui; Cai, Renfei; Li, Dongying; Wang, Li; Chen, Qiuju; Kuang, Yanping; et al. (Frontiers in Physiology, 2022)
Abstract Background: Many studies have demonstrated the positive clinical value of progestin-primed ovarian stimulation (PPOS) in polycystic ovary syndrome (PCOS) patients undergoing assisted reproductive technology. However, the underlying factors contributing to this phenomenon remain unclear. We conducted a retrospective observational study to compare the clinical outcomes of PCOS women undergoing PPOS or the short protocol to identify possible factors that influence outcome. Methods: This study included 304 patients undergoing PPOS and 152 patients undergoing short protocol from April 2014 to July 2019 after propensity-score matching. Human menopausal gonadotropin dose, hormone profile, embryo development and clinical outcomes of frozen-thawed transfer embryo cycles were compared. The primary outcome measure was implantation rate. Logistic regression was performed to identify contributing factors, and receiver operating characteristic curve analysis was used to calculate the cutoff of luteinizing hormone (LH) difference ratio in clinical outcomes. Results: Compared with the short protocol, PPOS resulted in a higher implantation rate (43.4% vs. 31.9%, P < 0.05), clinical pregnancy rate (61.8% vs. 47.4%, P < 0.05) and live birth rate (48.4% vs. 36.8%, P <0.05). Similar fertilization, cleavage and valid embryo rate per oocyte retrieved between groups were observed. The LH difference ratio was positively associated with implantation rate (P=0.027, OR=1.861, 95% CI: 1.074–3.226). The relationship between LH difference ratio with clinical outcomes was confirmed by receiver operating characteristic curve analysis and comparisons among patients grouped by LH difference ratio. Conclusions: The implantation rate was associated with the LH difference ratio during ovary stimulation in PCOS patients. Our results provide the explanation why PPOS shows positive clinical outcome for PCOS patients.